Carbon, Nitrogen, phosphorous and sulphur contents of Kanpur soils - S.P., Bhardwaj; A.N., Pathak (Journal of Soil and Water Conservation, 2022)
Carbon, Nitrogen, phosphorous and sulphur, the important elements of plant nutrition need no emphasis. The knowledge about the status of these elements in soil can give an idea about its fertility and can also predict, to some extent, the yield of crop to be grown there on. most of the soils of Kanpur district have got poor status of C, N, P and S.